Developing Aesthetic Thinking and Creative Decision-Making Skills in Ornamental Art - Aslonova Navro‘za Hoshim qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: Developing aesthetic thinking and creative decision-making skills is essential in ornamental art education. This article explores methods and pedagogical strategies that foster students’ ability to analyze, interpret, and create visually harmonious designs. By engaging in practical projects, group discussions, and reflective exercises, students enhance their capacity for aesthetic judgment, compositional planning, and innovative problem-solving. The study emphasizes the integration of traditional artistic principles with modern pedagogical approaches to promote creativity, critical thinking, and independent artistic decision-making. Findings indicate that structured exercises and guided practice significantly improve students’ aesthetic sensitivity and creative competencies.